2017
DOI: 10.1002/jmri.25868
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography is as accurate as liver biopsy for liver fibrosis staging

Abstract: 3. Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1268-1275.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 39 publications
0
41
0
2
Order By: Relevance
“…A meta‐analysis of lifestyle modification for NAFLD found that weight reductions of 4%‐14% resulted in significant relative reductions in intrahepatic fat levels of 35%‐81% . As in the LEAN study which found less worsening of fibrosis on serial liver biopsies in subjects on liraglutide (9% vs 36% with placebo), hepatic fibrosis, as measured with MR elastography which is comparably accurate to biopsy for fibrosis staging, decreased significantly and similarly in both groups. Hepatic fibrosis is an important predictor of morbidity and mortality in NAFLD …”
Section: Discussionmentioning
confidence: 91%
“…A meta‐analysis of lifestyle modification for NAFLD found that weight reductions of 4%‐14% resulted in significant relative reductions in intrahepatic fat levels of 35%‐81% . As in the LEAN study which found less worsening of fibrosis on serial liver biopsies in subjects on liraglutide (9% vs 36% with placebo), hepatic fibrosis, as measured with MR elastography which is comparably accurate to biopsy for fibrosis staging, decreased significantly and similarly in both groups. Hepatic fibrosis is an important predictor of morbidity and mortality in NAFLD …”
Section: Discussionmentioning
confidence: 91%
“…In this study, we used MRE instead of liver biopsy. Several studies have reported that MRE could be an alternative to liver biopsy [25,26]. The United States Food and Drug Administration (FDA) has approved MRE results without liver biopsy in NAFLD Phase IIa clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, liver biopsy samples 1/50,000th of the entire liver, and thus is susceptible to inadequate biopsy size, which can decrease accuracy of staging by 25% . Studies have shown that paired biopsies, from two different areas of the liver, can differ in histological fibrosis staging up to 40% of the time . Also, studies have demonstrated significant subjectivity in fibrosis staging, with different pathologists disagreeing on staging up to 50% of the time .…”
Section: Pros and Cons Of Methods Of Measurement Of Liver Fibrosismentioning
confidence: 99%
“…13 Studies have shown that paired biopsies, from two different areas of the liver, can differ in histological fibrosis staging up to 40% of the time. 14 Also, studies have demonstrated significant subjectivity in fibrosis staging, with different pathologists disagreeing on staging up to 50% of the time. 13,15,16 These inherent flaws in liver biopsy as a means for staging fibrosis in NAFLD have come to light only recently and further demonstrate the need for alternative methods (Table 1).…”
mentioning
confidence: 99%